Spatial Variability in High Value Crops – Initially Focused on Truffle Production in the South-West of Western Australia - Jackson, Erin Georgia Wilson (Curtin University, 2022)
Due to its aromatic quality, rarity, and cultivation difficulty, the Périgord black truffle is a highly valued commodity worldwide. Despite its value, current scientific knowledge is lacking, and limited research has occurred exploring which soil properties and climatic conditions have the highest influence over truffle yield. This research uses various spatial analysis methods to describe and map harvested truffles' spatial distribution within a truffière, over 3 harvest seasons. This spatial distribution was examined against climate data and various soil properties, to determine which factor(s) have highest influence over truffle yield.